Analysis of Gas, Oil, and Coal Company Performance during Pandemic of Covid-19: A Case Study of Indonesia - Kusmayadi, Dedi; Abdullah, Yusuf; Firmansyah, Irman (International Journal of Energy Economics and Policy, 2022)
Energy potential and demand in Indonesia continues to grow, especially for coal power generation needs. Likewise, energy needs derived from gas and oil for industrial, household, and transportation needs, even during the COVID-19 pandemic. Therefore, energy companies must have good performance to meet these needs. This study aims to determine the performance of energy companies, especially in gas & oil companies and coal companies, and the factors that influence them. The study was conducted in the last 3 years, namely 2018 to 2020 where there was a transition between before and during the pandemic. The study results found that there was a significant decrease between performance before the pandemic and during the pandemic. The decline was felt mainly by gas and oil companies. In addition, company size and liquidity are the most important factors to maintain the performance of energy companies. This is because the need for working capital to run an energy company is very large so that if it experiences a lack of funds, the company has the potential not to achieve the expected performance. In addition, of the two types of companies studied, coal companies significantly influence the performance of energy companies. This is in line with the huge energy demand from coal in Indonesia and the abundant coal reserves so that the opportunity to earn profits is greater than that of gas and oil companies.